Gamifikasi pembelajaran: Menerapkan elemen permainan untuk meningkatkan keterampilan matematika di era digital - Mukhlisoh, Yeni (Maliki Interdisciplinary Journal, 2024)
Mathematics education often faces challenges in engaging students interest and motivation, which can affect their learning outcomes. To address these challenges, innovative approaches such as gamification have been proposed. This research explores the effectiveness of game elements in enhancing students mathematical skills in the digital era, focusing on the educational context in Indonesia. Gamification offers elements such as points, badges, leaderboards, and missions to enhance student engagement and motivation. The interaction between different game elements can create a supportive and challenging learning environment, helping students develop problem-solving skills, critical thinking, and resilience in tackling mathematical problems. However, challenges such as differences in effectiveness between digital and non-digital games and the need to design game elements suitable for students' skill levels still need attention. Further research is needed to better understand how game elements can be tailored to various skill levels and student preferences, thereby enhancing the use of gamification in mathematics education in the future.